Variation in terpenoids and antioxidant activity of loquat flowers during post-harvest processing: a metabolomics study - Duan, Mingzheng; Feng, Jinghan; Gu, Na; Tao, Qinxin; Wang, Xue; Li, Jing; Liu, Zengqun; Duan, Xiande; Wan, Tongfa; Rao, Muhammad Junaid (Frontiers in Plant Science, 2026)
Loquat (Eriobotrya japonica) flowers are an underutilized resource rich in bioactive compounds, yet the impact of post-harvest processing on their chemical composition remains poorly understood. This study employed a widely targeted metabolomics approach using UPLC-MS/MS with electrospray ionization in both positive and negative modes (ESI+/ESI-) to investigate how different processing methods, including fresh samples (FS), heat-drying (HD), freeze-drying (FD), and subsequent hot-water extraction (FSP, HDP, FDP), affect the terpenoid profile and antioxidant capacity of loquat flowers. A total of 193 terpenoids were identified. Freeze-drying best preserved the native terpenoid diversity and yielded the highest total content, whereas heat-drying led to significant alterations. Multivariate analyses (PCA, HCA) revealed that the hot-water extraction process itself was the dominant factor, inducing a more profound shift in the terpenoid profile than the initial drying method. This was evidenced by terpenoid content reductions ranging from 59% to 70.7% in the hot-water extracts compared to their raw materials. Accordingly, the highest antioxidant activity was found in the freeze-dried sample (469.38 μg Trolox per gram dry weight) but was markedly reduced in all hot-water extracts (143.39-189.54 μg Trolox per gram extract powder). Thus, processing critically defines product quality, with freeze-drying recommended for terpenoid preservation, while extraction optimization is essential to harness the maximum nutraceutical potential of loquat flowers.